2020
DOI: 10.5937/ijcrsee2001001k
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Style Predictors of the Students’ Psychological Well-Being

Abstract: The article analyses the psychological well-being and basic beliefs of students from the point of view of various variables, but the particular attention is payed to cognitive style, which is studied as the way of information assessment, determining person's intellectual activity as well as own life activity in general. Theoretical and multivariate regression (stepwise method) analyses allowed us to define the models of psychological well-being and basic beliefs predictors at the significance levels from p≤0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
3
0
2
Order By: Relevance
“…Взаимосвязь когнитивных компонентов СБ с когнитивно-регуляторными процессами осознанной саморегуляции показывает, что ориентация на достижение цели всегда связана с более высокими уровнями субъективного благополучия, что подтверждается и другими исследованиями Kibalchenko, Eksakusto, 2020;.…”
Section: обсуждение результатовunclassified
See 1 more Smart Citation
“…Взаимосвязь когнитивных компонентов СБ с когнитивно-регуляторными процессами осознанной саморегуляции показывает, что ориентация на достижение цели всегда связана с более высокими уровнями субъективного благополучия, что подтверждается и другими исследованиями Kibalchenko, Eksakusto, 2020;.…”
Section: обсуждение результатовunclassified
“…Индивидуально-психологический уровень субъективного благополучия. В последние десятилетия понимание СБ стало конвергироваться на сугубо индивидуальных критериях, вокруг личностной основы, стабильных личностных диспозициях, внутреннем мире субъекта, опосредованном социокультурными предпосылками образа жизни, что получило эмпирическое подтверждение (Kibalchenko, Eksakusto, 2020;.…”
Section: Introductionunclassified
“…Thus, open-minded cognition is an effective cognitive method of processing information and one of the measures of metacognitive experience formation, person's intellectual development level and being successful in intellectual activity (Kibal'chenko and Eksakusto, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, cognitive conflicts are formed and are related to the cognitive structure of the individual and their environment (Chang et al, 2009). There are several opinions of several experts who reveal how cognitive conflict is built: (1) cognitive imbalance, namely; an imbalance between a person's cognitive structure and the information that comes from their environment, in other words, there is an imbalance between internal structures and external inputs (Piaget, 1964); (2) cognitive imbalance or metacognitive conflict, namely: a conflict between schemata where there is a conflict between the old cognitive structure and the new cognitive structure (which is being studied or faced) (Chang et al, 2009;Kibalchenko & Eksakusto, 2020) and (3) Cognitive conflict, namely the conflict between new cognitive structures (involving newly studied material) and an environment that can be explained but the explanation refers to the initial cognitive structures possessed by individuals (Lee & Kwon, 2001). Some of the opinions put forward by experts can be concluded that cognitive conflict is a condition in which the new information it receives does not match the existing cognitive structure.…”
Section: Introductionmentioning
confidence: 99%